Antioxidant and antimicrobial modified cellulose nanofibers for food applications. (December 2021) - LakshmiBalasubramaniam, SuriyaPrakaash; Patel, Avinash Singh; Nayak, Balunkeswar; Howell, Caitlin; Skonberg, Denise
Abstract: Cellulose nanofibers (CNF) are renewable, biodegradable, and non-toxic biopolymers; however, they have not been widely adopted as an additive by the food industry. In this study, CNF functionality was improved through chemical modification. Antioxidant and antimicrobial nanofibers were produced through the esterification of CNF with phenolic acids. CNF were esterified with vanillic or cinnamic acid using two different esterifying agents: thionyl chloride and 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC). Modified fibers from the four different treatments were evaluated for their structural properties, antioxidant properties, thermal stability, dispersibility and antimicrobial properties. Both esterifying agents successfully produced phenolic acid esterified CNF fibers. Vanillic acid modified fibers showed better antioxidant activity (70% DPPH radical scavenging activity) than cinnamic acid modified fibers (10% DPPH scavenging activity). In contrast, cinnamic acid modified fibers showed better antimicrobial activity against Staphylococcus epidermidis . Thermal stability depended on the esterifying agent utilized; the use of thionyl chloride (DTG max 260.19 ± 1.38 °C) significantly (p < 0.05) reduced the thermal stability of modified fibers while EDC (DTG max 326.09 ± 0.49 °C) did not. When the modified CNF fibers were added to a model food (canola oil), a significant effect (p < 0.05) on lipid oxidation during storage depending on the type of CNF fiber used was observed. When compared to CNF, EDC modified fibers improved the oxidative stability of the canola oil while thionyl chloride modified fibers did not. These results suggest that esterification with phenolic acids can impart antimicrobial and antioxidant functionality to CNF food additives that have the potential to prolong the shelf life of foods. Graphical abstract: Image 1